An autosomal dominant multiple pterygium syndrome. Issue 2 (February 1988) - McKeown, C M; Harris, R
Abstract : Three sibs and their mother with features of a multiple pterygium syndrome are reported. Inheritance in this family is consistent with autosomal dominant inheritance with great variation in severity between affected subjects. The importance of examining other family members closely in cases of multiple pterygium is emphasised.